EVALUATION OF APOPTOGENIC EFFECTS OF AVERRHOA BILIMBI EXTRACT ON EHRLICH ASCITES CARCINOMA BEARING MICE - Chauhan, Jyoti B; KS, Balaji; S, Jayarama; Kapfo, Wethroe (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The proapoptotic potential of aqueous methanol extract of Averrhoa bilimbi fruit (AMBE) in vivo against Ehrlich ascites carcinoma (EAC) bearing Swiss albino mice was studied. Methods: Cytotoxicity of the extract on the EAC cells was monitored by tumor growth response, trypan blue exclusion assay, Giemsa staining, DNA fragmentation, fluorescence-activated cell sorting (FACS) analysis, and reverse transcription-polymerase chain reaction (RT-PCR). The phytochemical screening using LC-MS and Fourier transform infrared (FT-IR) was conducted. Results: The extract at 100 mg/kg body weight was significantly cytotoxic toward the cells with approximately 73% growth inhibition on day 12. It markedly decreased the tumor volume by 65% and viable tumor cell by 72%. Giemsa staining of AMBE treated cells displayed apoptotic morphologies such as membrane blebbing, cytoplasmic condensation, and apoptotic bodies. Cytotoxicity of the extract to the carcinoma cells through apoptosis was further highlighted by DNA fragmentation in treated cells, while FACS analysis showed that growth arrest took place at G0/G1 phase. RT-PCR analysis displayed reduced level of Bcl-2/Bax ratio in test cells as compared to control cells. Phytochemical analysis of the extract using LC-MS and FT-IR studies showed that protocatechuic acid was the predominant component present in the extract. Conclusion: Our studies indicated that Averrhoa bilimbi extract expressed significant apoptogenic potential against EAC cells in vivo. Keywords: Ehrlich ascites carcinoma, Apoptosis, Fluorescence-activated cell sorting, Bax/Bcl-2, Protocatechuic acid.